Right Paraduodenal Hernia: A Case Report and Literature Review - Alabdulaaly, Dr. Norah; Alshehri, Dr. Mohammed Ali; Alsannaa, Dr. Feras (International Journal of Innovative Research in Medical Science, 2022)
Paraduodenal hernia is a rare congenital anomaly that arises from an error of rotation of the midgut. The duodenum and the small intestine become trapped in a sac which is lined by the peritoneum, behind the mesentery of the colon, either to the right or left of the midline. It is therefore a rare and potentially life-threatening condition that can cause intestinal obstruction progressing to strangulation and perforation. The present report shows the case of right paraduodenal hernia in a 21 years old patient, Diagnosed with CT scan and underwent a surgical successful management.